Genetic characterisation of two humped camel of India (Camelus bactrianus) - BANERJEE, PRIYANKA; JOSHI, JYOTI; S, UPASNA; GANAI, NAZIR; VIJH, R K (The Indian Journal of Animal Sciences, 2012)
Microsatellite data was generated on 17 bactrian camels using 27 markers. The data analysis revealed a fair degree of heterozygosity existing in these bactrian camel which are very few in number (149). The mean heterozygosity and effective number of alleles were 0.56 and 3.89 respectively. The F statistics also revealed normal rate of inbreeding in this stock. This was attributed to free flow of bactrian camel germplasm between valley and Tibetan plateau till recent times. The population constancy was also established using inter and intralocus tests. Effective conservation measures are suggested owing to small number of individuals and systematic mating plan is advocated.